Tourniquet use during knee arthroplasty: a Bayesian network meta-analysis on pain, function, and thromboembolism - Migliorini, Filippo; Maffulli, Nicola; Eschweiler, Jörg; Knobe, Matthias; Tingart, Markus; Betsch, Marcel (The surgeon, 2022)
Background - The role of a tourniquet for knee arthroplasty remains controversial. The present Bayesian network meta-analysis investigated the role of various protocols for tourniquet inflation for knee arthroplasty, assessing data on pain control, clinical and functional outcomes, and the rate of deep vein thrombosis (DVT). - Material and methods - The present Bayesian network meta-analysis was conducted according to the PRISMA guidelines. In March 2021, all clinical trials investigating the role of tourniquet use for knee arthroplasty were considered for inclusion. Groups were divided into those which used a tourniquet in knee arthroplasty procedures versus those which completed the procedure without tourniquet, or with varying protocols of tourniquet use. The hierarchical random-effects model analysis was adopted in all comparisons. - Results - Data from 54 articles (5497 procedures) were retrieved. The absence of tourniquet group evidenced the lowest rate of DVT, and scored the lowest in the visual analogic scale (VAS) at 24-48 h, 1, 3, and 12 months follow-up. The same group evidenced the greatest gain of motion at 3-days, 1 week, 1 month, 3 months, 6 months, and 12 months follow-up, and the highest Knee Society Rating System scores at 1, 3, and 12 months follow-up. Of the outcome data assessed, the straight-leg-raise test was markedly inconsistent: therefore, no recommendations from this test can be made. - Conclusion - With regards to the endpoints considered in the present study, knee arthroplasties undertaken without the use of a tourniquet perform better overall.